The Effects of the Family-oriented Empowerment Model on the Fatigue Level of the Patients with Chronic Obstructive Pulmonary Disease Admitted to the Hospitals Affiliated to Shahrekord University of Medical Sciences, Iran (2018) - A Hassanpour Dehkordi; F Soleymani; Z Habibi; S Kheiri; SH Salehitali (Iran University of Medical Sciences, 2020)
Background & Aims: Fatigue in patients with chronic obstructive pulmonary disease reduces their professional productivity, concentration, sex drive, and performance, leading them toward lethargy. Overcoming this issue requires the involvement of the patient and the family in the care and management of the disease. The present study aimed to investigate the effects of the family-oriented empowerment model on the fatigue level of patients with chronic obstructive pulmonary disease. Materials & Methods: This clinical trial was conducted on 72 patients with chronic obstructive pulmonary disease and their family caregivers. The subjects were selected via convenience sampling and randomly divided into two groups of intervention and control (36 per each). The family-oriented empowerment training program was implemented in four 90-minute sessions based on the four steps of perceived threat, problem-solving, educational participation, and evaluation in groups of 10-15 participants in the presence of the family members in the form of a panel for the intervention group. The intervention group was followed-up by the research team for three months to respond to the issues, care problems, and knowledge required for care. The final evaluation was performed three months after the intervention by completing the fatigue questionnaire again. Data analysis was performed in SPSS using paired t-test, independent t-test, Fisher's exact test, and Chi-square. Results: At baseline, the intervention and control groups had no significant difference in terms of the mean score of fatigue (P=0.5). After the intervention, the mean score of fatigue in the intervention group was significantly different from the control group (P=0.01). In addition, the mean score of fatigue significantly decreased after the intervention compared to before the intervention (P<0.001). Conclusion: According to the results, the empowerment of the family members responsible for the care of the patients with chronic obstructive pulmonary disease could decrease fatigue in the patients. Therefore, the healthcare programs of chronic patients should be focused on the caregivers of the patients in addition to the patients.